ESTUDO PARA APLICAÇÃO DE ELETRIFICAÇÃO FOTOVOLTAICA RURAL DESCENTRALIZADA NO MUNICÍPIO DE ITABORAÍ - Perrotta, Patrícia Freire Iorio (2011)
With low economic growth during decades Itaborai suffered from insufficient public policies, causing a lack of basic infrastructure, including power distribution. Itaborai was considered a major agricultural centre and mill by ease of disposal of the products through its port at the end of the eighteenth century and had its consolidated economic importance in the middle nineteenth century with the deployment of the first stretch of railroad, since entire genres was entitled do Norte Fluminense by railroad and sent to the port. The decline of Itaborai was one of the main reasons for the construction of the road connecting the Guanabara Bay to North Fluminense, ending its status as commercial warehouse. With the return of economic growth of the city with the construction of the Petrochemical Complex of the State of Rio de Janeiro, demanding greater efficiency in public services, the aspect related to insufficient infrastructure became more evident. One of the populations most affected is the resident in rural areas of the municipality, where co-ops provide energy at relatively high cost for that population and inconstant. In this context are examined some aspects of environmental sustainability and economic viability for the implantation of a system of decentralized photovoltaics in rural subsistence production population areas, as well as aspects related to your deployment through public policies. With regard to the aspect of environmental sustainability are valued geomorphological conditions and the weather data, such as the insolation, monitored daily in the city, as well as the positive and negative impacts ascending from the implementation of the system, its interface with the guidelines set out in the COMPERJ licensing process and the ways and legal instruments which will foster the deployment of even, for better performance in its environmental licensing process. Among the economic aspects for the implementation of the system are analyzed the costs of deployment and maintenance of it, in order to give the future user just the maintenance cost, reducing in this way the cost with electric power, in addition to the study of forms of funding and partnerships for viability of deployment of the proposed system.